Cynicism among medical students: An in-depth analysis of mental health dynamics and protective factors in medical education using structural equation modeling - András Spányik; Dávid Simon; Adrien Rigó; Boróka Gács; Nóra Faubl; Zsuzsanna Füzesi; Mark D. Griffiths; Zsolt Demetrovics (PLoS ONE, 2025)
Background Medical students frequently grapple with challenges during their studies, including emotional impacts, career socialization, psychiatric comorbidities, and burnout syndrome. Burnout syndrome profoundly influences mental and physical health, impacting patient care. Within this complex landscape, elevated stress levels specifically manifest in increased cynicism, reduced idealism, and other mental health issues. The simultaneous decline of empathy during medical education adds a layer of complexity. Understanding these dynamics and the potential protective factors is crucial for addressing students’ well-being and optimizing curriculum development. Methods The present study comprised third-year and fifth-year Hungarian medical students from the University of Pécs in a partially cross-sectional, partially longitudinal investigation conducted at two time points (2018/19: 124 third-years; 127 fifth-years; 2020/21: 82 third-years; 37 fifth-years). All medical students were sampled in the given year of the selected semester (third-year students at the first timepoint were asked once again as fifth-year students at the second timepoint). In addition to descriptive statistics, structural equation modelling was used to assess the impact of time, role model, perceived stress, empathy, and burnout on medical students. Results The analysis indicated that there was a significant increase in cynicism during the institutional socialization of medical students. While there was only partial support for the reduction in the perception of patient-centered role models during institutional socialization, the findings indicated that the perception of patient-centered role models and empathy acted as protective factors mitigating cynicism. Unexpectedly, the analysis found an increase in stress and cynicism over time, possibly influenced by factors such as the COVID-19 pandemic. Conclusion The study’s findings indicate a rise in cynicism among medical students over time that could threaten future doctor-patient relationships. The findings emphasize the protective role of empathy and patient-centered role models, emphasizing the need for humanistic integration in medical education.